The Family Role in Fulfilling the Activities of Daily Living (ADLs) among Children with Autism Spectrum Disorder - Suprajitno Suprajitno; Frizcha Illah Arisky (Journal of Ners and Midwifery, 2019)
Children with autism spectrum disorder (ASD) have difficulty of activity and readability so that dependently to a parent or others. The study purpose to describe the family role in fulfilling of the Activities of Daily Living (ADLs) for children with ASD who gets service at Autism Center of Blitar City (Bahasa: Pusat Layanan Autis Kota Blitar). The study used descriptive-survey as a design to determine family roles among ASD children, the researcher purposively selected 34 families to be part of the study. Questionnaires were developed inspired by the theory of basic human needs and self-care and underwent validity and reliability tests. This study result showed that the family role in fulfilling the ADLs for children with ASD in the good category as many as 67.6% (23 families), in enough category as many as 29.4% (10 families), and in less category as many as 3.0% (1 family). Fulfillment of ADLs for children with ASD who need attention is the fulfillment of nutrition because parents must ensure that food that has entered into the mouth should be swallowed. Results also found out that inadequate nutrition affects childâ€™s with ASD growth and development. The study strongly recommends the roles of parents as vital in meeting the needs of the childrenÂ  and stimulates development.